Classical soloists' life histories and the music conservatoire. (May 2021) - Palmer, Tim; Baker, David
This article explores the life histories of virtuoso classical music soloists with particular reference to conservatoire provision. Detailed life-history interviews were conducted with six virtuosi between May 2018 and January 2019. These participants were three singers, two cellists and a concert pianist. Resultant qualitative data were stored in an NVivo software database and understood through a process of analytic induction. Key findings spotlight the significance of Higher Education, a connection between broad creative and cultural interest and musical excellence, and a significant role for conservatoires in diversifying their training and easing transition into the career. The soloists also warned of dangers relating to controlling teachers, loss of autonomy and a need to convey their career realities to students.